1978
DOI: 10.1042/bj1740283
|View full text |Cite
|
Sign up to set email alerts
|

A protein-glucan intermediate during paramylon synthesis

Abstract: A sodium deoxycholate extract containing glucosyltransferase activity was obtained from a particulate preparation from Euglena gracilis. It transferred glucose from UDP-[14C]glucose into material that was precipitated by trichloroacetic acid. This material released beta-(1 leads to 3)-glucan oligosaccharides into solution on incubation with weak acid, weak alkali and beta-(1 leads to 3)-glucosidase. The products of the incubation of the deoxycholate extract with UDP-[14C]glucose were analysed by sodium dodecyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Paramylon is synthesized by membranebound paramylon synthases (UDP-glucose:β-1,3-glucan β-glucosyltransferase), that preferentially uses UDP-glucose (but not ADPglucose) as the glucose donor (Marechal and Goldemberg 1964;Tomos and Northcote 1978). A recent comprehensive gene expression analysis of Euglena identified two probable paramylon synthases, which have 14 and 19 membrane spanning domains (Yoshida et al 2016).…”
Section: Degradation Of Paramylonmentioning
confidence: 99%
“…Paramylon is synthesized by membranebound paramylon synthases (UDP-glucose:β-1,3-glucan β-glucosyltransferase), that preferentially uses UDP-glucose (but not ADPglucose) as the glucose donor (Marechal and Goldemberg 1964;Tomos and Northcote 1978). A recent comprehensive gene expression analysis of Euglena identified two probable paramylon synthases, which have 14 and 19 membrane spanning domains (Yoshida et al 2016).…”
Section: Degradation Of Paramylonmentioning
confidence: 99%
“…It must be stressed that "-1,3-linked storage "-glucans are widely distributed in the bikont branch of the eukaryotes (Fig. 4.1, see legend for definition of bikont) and that very few reports address the biochemistry of their synthesis or mobilization (Bäumer et al 2001;Goldemberg and Marechal 1963;Tomos and Northcote 1978;Vogel and Barber 1968). Most soluble "-glucan forms, such as laminarin, chrysolaminarin, and mycolaminarin, contain, in addition, "-1,6 branches, while the very highly crystalline paramylon found in Euglena (an excavate unicellular green alga) and Traditionally the eukaryotes are divided into the unikonts and bikonts which were previously thought to contain only uniflagellated cells or biflagellated cells.…”
Section: The Bacterial Eukaryote and Archeal Domainsmentioning
confidence: 99%
“…The enzyme, which is associated with particles, was highly specific for the donor substrate, since ADPG, TDPG, and UDP-f3-D-glucose were inactive, and apparently did not require an external primer. This latter aspect has been examined by TOMOS and NORTHCOTE (1978) who concluded that paramylon was, in fact, synthesized on to a protein rather than carbohydrate primer. The bond linking the glucan to the protein was tentatively identified as a pyrophosphate linkage.…”
Section: The Metabolism Of Paramylonmentioning
confidence: 97%